'I felt like I was watching porn': the reality of preparing pre-service teachers to teach about sexual pleasure. Issue 3 (3rd May 2016) - Ollis, Debbie
Abstract: Overwhelmingly, school-based sexuality education programmes focus on the prevention of infection, pregnancy and abuse, with little if any attention given to positive views of sexuality and rarely the inclusion of sex positive issues such as pleasure, intimacy and desire. This paper explores the experience of teaching about pleasure to pre-service health and physical education teachers as part of compulsory studies in a unit on sexuality education designed to prepare them to teach sexuality education in secondary schools. Drawing on the aims, theoretical framework, content and pedagogical structure of the unit, and data collected from 42, third-year pre-service teachers (PST) in Australia via surveys and student assessment, the paper provides some practical examples of what teaching about pleasure might look like in practice. It argues that with adequate preparation, a framework to celebrate sex and sexuality, a gender lens to examine normative discourses, and the opportunity for reflection, PST can develop the confidence, skill and willingness to include pedagogies of pleasure in their school-based work.